What is Important For You (WIFY) dan Life Map berbasis Goal Attaintment Model terhadap Self Care Behaviour pada Pasien Diabetes Melitus Tipe 2 - Kusnanto Kusnanto; Moh Zen Arifin; Ira Suarilah; Hidayat Arifin (Jurnal Ilmiah Kesehatan, 2019)
Introduction: Diabetes mellitus was an uncurable metabolic disease but it can be controlled. Diabetes can be controlled independently by diabetic with diabetes self-care behavior. Self-care behavior was challenge problem causing in adherence in majority diabetic clients especially in Persadia Darmo Hospital. Method: Research design was Quasy-Experiment study among type 2 diabetic client. This study involved 30 samples taken by purposive sampling. The independent variable were What is Important For You (WIFY) and Life Map. The dependent variable was self-care behavior. Data were taken by using SDSCA questionnaire then analyzed by using t-test with a= £0.05. Result and Analyze: WIFY and Life Map change self-care behavior in treatment group before and after treatment significantly with p value = 0,024. There was significant difference between treatment and control group of self-care behavior with p value = 0,029. Discussion: It could be concluded that application of WIFY and Life Map with goal attainment model increase self-care behavior in type 2 diabetic clients. The use of this approach could be optimizing diabetic counseling and education for clients. Further research to investigate WIFY and Life map effect on blood glucose level and HbA1c test in Type 2 Diabetic.